L'efficacia della musica a scuola: una rassegna delle evidenze - Amalia Lavinia Rizzo; Marta Pellegrini (LED Edizioni Universitarie, 2021)
The Italian school legislation supports the educational use of music from preschool to lower secondary school for the improvement of skills included in the student's profile at the end of the first cycle of education. In the framework of inclusive education, musical teaching is part of the school's commitment to promote the development of academic skills, executive functions, self-regulation as well as emotional, affective, and social dimensions. All those elements are needed for improving learning and developing attitudes towards the consideration of the differences. This work presents an umbrella review of the evidence on the effectiveness of educational musical activities for the improvement of cognitive skills, socio-emotional skills, and school performance from pupils attending K-12 as well as the factors that are relevant for improving the quality of music interventions in school. The review includes meta-analyses already conducted on the effectiveness of music and presents the method adopted for searching, selecting, and coding the studies. By reviewing the evidence, it emerges the need to carry out new research in the field of music teaching that should be more rigorous in the method than the ones included in this umbrella review.